AB0746 Frequency and clinical association of rare antibodies in a large connective tissue disease cohort. (12th June 2018) - Campochiaro, C.; Clark, K.; Host, L.; Sari, A.; Nihtyanova, S.; Fonseca, C.; Denton, C.; Ong, V.
Abstract : Background: Connective tissue diseases(CTDs) are characterised by the presence of specific antibodies(Abs). These are useful in diagnosis and prognostic stratification. Rare Abs have been reported but their clinical significance is currently not as clear. Objectives: to assess the diagnosis, and frequency of clinical features within each rare antibody subgroup in our CTD cohort Methods: The immunology results for 5828 patients obtained over the past 17 years and patients positive for 1 of the rare Abs (Jo-1, PCNA, XR, PL-4, PL-7, PL-12, SRP, Ku, Mi-2, EJ, SL, PmScl, rRNP, Th/To, NuMa-1, OJ and hnRNP) were identified. Diagnosis and frequency of major organ involvement were reported. Results: 758 patients(12.5%) were positive for at >1 rare Abs. Clinical information confirming a diagnosis of a CTD was available for 514 patients. The most frequent rare Ab in our cohort was PmScl(3.10%). The majority of patients had clinical features of overlap syndromes(33.8%), the 2nd most common diagnosis was systemic sclerosis(SSc)(31.10%). Interstitial lung disease(ILD) was more commonly seen in patients with PL-7+(82.4%), PL-12+(75%), Jo-1+(70.8%) and SRP+(66.7%). ILD was not reported in PCNA+, PL-4+, NuMA-1+and hnRNP+. Pulmonary arterial hypertension(PAH) was most frequently seen in patients with XR+(31.8%). Inflammatory myositis(IM) was found in all Jo1 +and SRP +patients, and in the majority of PL-7+(88.2%) patients. Inflammatory arthritis was commonly reported in patients with PCNA+(57.1%), NuMA-1+(50.0%) and rRNP+(40%). Renal involvement was classified as either glomerulonephritis(GMN) or scleroderma renal crisis(SRC). GMN was more common in patients with rRNP+(60%), PL-4+(45.4%) and PCNA+(42.9%) patients. SRC was diagnosed in patients with SL+(3.2%), PM/Scl+(5.5%) and Th/To+(2.5%) (table 1). Conclusions: Our data from a large CTD cohort suggest that rare Abs associate with distinct features in particular ILD and inflammatory myositis. A majority of these patients fulfil the criteria for overlap syndrome and SSc. Disclosure of Interest: None declared